Technical and institutional factors affecting the introduction of electrothermal consumers-controllers in district heating systems - Derii V.O. (General Energy Institute of the National Academy of Sciences of Ukraine, 2014)
The results of studies have demonstrated that the introduction of electrothermal consumers-controllers in district heating systems causes significant fluctuations of heat power in these systems. To smooth such fluctuations, it is necessary to accumulate heat energy in district heating networks. Because of this, the power system operator which controls the electrothermal consumers-controllers should consider some characteristic features of district heating systems, such as changes in heat load, the procedure for supplying heat to consumers, and the parameters of the heat carrier. The district heating system operator should also consider, additionally to ambient temperature, such a destabilizing factor as the excess capacity of the electrothermal consumers-controllers. In this case, the operator cannot control the district heating system according to the temperature chart only. In order to ensure the reliable performance of a centralized heat supply system, it is necessary to develop and implement the corresponding algorithm of interaction between the power system operator and the district heating system operator and provide the required software and hardware. The results of the analysis performed have provided the possibility to determine limiting factors for heat supply systems, limiting rates of changes in the capacity of the electrothermal consumers-controllers, and time periods required to prevent a decrease in the capacity of the system heat generators. The results of the analysis have also demonstrated the necessity to develop legal documents regulating the operation of electrothermal consumers-controllers.